Effect of exogenous pulmonary surfactant on infectious pneumonia, serum procalcitonin, high-sensitivity C-reactive protein and interleukin-6 in neonates (Indian Journal of Experimental Biology (IJEB), 2023)
Infectious pneumonia common among neonates has morbidity rate as high as 25%. Proper clinical diagnosis with treatment for respiratory and circulatory failure may prevent mortality. Neonates with infectious pneumonia are mostly treated with mechanical ventilation, antibiotics and pulmonary surfactant. Here, we assessed the effects of exogenous pulmonary surfactant on neonatal infectious pneumonia (NIP). A total of 120 neonates treated from October 2019 to December 2020 were randomly divided into control and observation groups (n=60). Control group received conventional treatment for 7 d, based on which observation group was given 100 mg/kg PS. Their blood gas indices, oxygenation status, lung consolidation and levels of serum procalcitonin (PCT), high-sensitivity C-reactive protein (hs-CRP) and interleukin-6 (IL-6) were compared. Partial pressure of oxygen (PaO2) increased, while that of carbon dioxide (PaCO2) decreased 24 and 48 h after treatment compared with those before treatment, and the observation group had higher PaO2 and lower PaCO2 (P